2015
DOI: 10.3390/ijms16035555
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Inhibits Glutamate Release in Rat Cerebrocortical Nerve Terminals

Abstract: The effect of palmitoylethanolamide (PEA), an endogenous fatty acid amide displaying neuroprotective actions, on glutamate release from rat cerebrocortical nerve terminals (synaptosomes) was investigated. PEA inhibited the Ca2+-dependent release of glutamate, which was triggered by exposing synaptosomes to the potassium channel blocker 4-aminopyridine. This release inhibition was concentration dependent, associated with a reduction in cytosolic Ca2+ concentration, and not due to a change in synaptosomal membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Accordingly, several studies suggested a key role for CB 1 receptors activation in cannabinoid neuroprotection. In agreement, CB 1 R-knockout mice have been reported to be more sensitive to inflammatory and excitotoxic insults than control animals (Pryce et al, 2003) and activation of CB 1 receptors elicits inhibitory effects by reducing glutamate release (Howlett et al, 2004;Lin et al, 2015). Interestingly, Gobira et al (2015) suggested that cannabidiol, a non-psychotomimetic constituent of Cannabis sativa, shows neuroprotection reducing glutamate release through activation of mTOR pathway.…”
Section: Cannabinoidsmentioning
confidence: 79%
See 1 more Smart Citation
“…Accordingly, several studies suggested a key role for CB 1 receptors activation in cannabinoid neuroprotection. In agreement, CB 1 R-knockout mice have been reported to be more sensitive to inflammatory and excitotoxic insults than control animals (Pryce et al, 2003) and activation of CB 1 receptors elicits inhibitory effects by reducing glutamate release (Howlett et al, 2004;Lin et al, 2015). Interestingly, Gobira et al (2015) suggested that cannabidiol, a non-psychotomimetic constituent of Cannabis sativa, shows neuroprotection reducing glutamate release through activation of mTOR pathway.…”
Section: Cannabinoidsmentioning
confidence: 79%
“…(Tomida et al, 2004;Yazulla, 2008). Interestingly, some studies suggested that inhibition of glutamate release represents a key mechanism involved in neuroprotection mediated by the cannabinoid system (Braida et al, 2000;Sinor et al, 2000;Marsicano et al, 2003;Gobira et al, 2015;Lin et al, 2015). In 2007, our group using an animal model of acute glaucoma reported that inhibition of fatty acid amide hydrolase (FAAH) or administration of metanandamide, a stable analogue of anandamide, minimize RGC loss caused by ischemia/reperfusion and that MK801, a noncompetitive NMDA receptors antagonist, controls anandamide degradation through FAAH (Nucci et al, 2007b).…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Moreover, PEA is an endogenous molecule in humans and many other living organisms that can play a very important role in maintaining cellular homeostasis and in counteracting exogenous stressful events that can lead to an inflammatory reaction. Among the pharmacological strategies for sensory and affective/cognitive disorders associated with neuropathic pain, PEA showed anti-inflammatory, analgesic, immunomodulatory and neuroprotective effects as well [ 3 , 4 , 5 ] by restoring glutamatergic transmission homeostasis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. For example, PEA demonstrates a neuroprotective action in experimental models of neuroinflammation and neuropathic pain mediated by mast cells and in experimental models of stroke, spinal injury, traumatic brain injury and Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, PEA has been reported to inhibit glutamate release in rat cerebrocortical nerve terminals. 27 Previously, we compared alterations of circulating levels of eCBs and NAEs 28,29 and glutamate 30 in subjects with chronic widespread pain and healthy controls (HC); however, no clear biological roles of this alteration were determined. Here, we investigate the effect of a 30-min dynamic load arm cycling intervention with respect to circulating levels of eCBs, NAEs and glutamate in subjects with chronic neck and shoulder pain (CNSP) and in HC.…”
Section: Introductionmentioning
confidence: 99%